2021
DOI: 10.3390/polym13244395
|View full text |Cite
|
Sign up to set email alerts
|

Monomer Elution from Three Resin Composites at Two Different Time Interval Using High Performance Liquid Chromatography—An In-Vitro Study

Abstract: Esthetics, improved colour stability and ease of contour have made photo-activated resin based restorative materials being widely used in routine dental clinical practice. Perhaps improper and inadequate polymerization of resin based composite material might lead to elution of monomer. Thus, the aim of the current study was to quantify the monomer elution from three resin composites. The intended analysis was made using high performance liquid chromatography (HPLC) at two different time periods. Three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…With higher monomer concentrations in the samples stored for 1 month compared to those stored for 24 h and 7 days, it was found in the present study that increasing the storage time resulted in higher amounts of Bis GMA and DMA BEE elution for all Tetric and Filtek composites, as noted in the study by Janani et al [ 46 ]. Nazar at al.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With higher monomer concentrations in the samples stored for 1 month compared to those stored for 24 h and 7 days, it was found in the present study that increasing the storage time resulted in higher amounts of Bis GMA and DMA BEE elution for all Tetric and Filtek composites, as noted in the study by Janani et al [ 46 ]. Nazar at al.…”
Section: Discussionsupporting
confidence: 81%
“…also used high-performance liquid chromatography analysis and reported that longer storage times resulted in statistically significant increases in BisGMA and UDMA amounts for both Tetric and Filtek materials [ 47 ]. There are few studies investigating the long-term elution of monomers over 1, 3, and 12 months using liquid chromatography tandem mass spectrometry and high-performance liquid chromatography [ 16 , 46 ]. However, the long-term effects of residual monomers on biocompatibility are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…27 The U.S. Food and Drug Administration (FDA) has graded a 75% ethanolwater solution as clinical oral stimulating liquid and it has been used in several studies. 28 In our study, we incorporated a 70% ethanol-water solution as one of our storage solutions and the elution of TEGDMA was high in ethanol as compared to other solutions. It can further be justified by the fact that ethanol has the ability to penetrate within the unreacted monomer and widens the gap within the polymer chains, allowing the soluble compounds to elute.…”
Section: Discussionmentioning
confidence: 99%
“…Metal compounds, though, are present in all endodontic sealers, and their values can vary on interaction with different irrigants used in endodontics, eventually influencing the outcome in the long run. One of the limitations of the present study is the use of a tooth model; though it better simulates clinical conditions, the results achieved could vary when done in vivo, based on a multitude of factors such as clinician’s irrigation preferences, treatment protocol, endodontic irrigant concentration, the tooth of treatment, and canal morphology [ 52 , 53 ]. Though the use of different final irrigation protocols in the assessed teeth would not necessarily replicate the clinical scenario, it was nevertheless conducted since the primary aim was to assess if endodontic irrigants present on the internal dentinal surface had an influence on the properties of the endodontic sealers.…”
Section: Strength Limitations and Future Directionsmentioning
confidence: 99%